2019
DOI: 10.1029/2018ja026193
|View full text |Cite
|
Sign up to set email alerts
|

Subauroral Neutral Wind Driving and Its Feedback to SAPS During the 17 March 2013 Geomagnetic Storm

Abstract: Subauroral Polarization Streams (SAPS) are associated with closure of region 2 field-aligned current (R2 FAC) through the low conductivity region. Although SAPS have often been studied from a magnetosphere-ionosphere coupling perspective, recent observations suggest strong interaction also exists between SAPS and the thermosphere. Our study focuses on thermospheric wind driving and its impact on SAPS and R2 FAC during the 17 March 2013 geomagnetic storm using both observations and the physics-based Rice Convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 55 publications
(70 reference statements)
5
34
0
Order By: Relevance
“…This time difference is almost consistent with our observational results. Ferdousi et al (2019) also showed that the electron density enhancement appeared in the daytime (10:00–16:00 MLT) midlatitude region (50–60° GMLAT) in the results of the physics‐based Rice Convection Model‐Coupled Thermosphere, Ionosphere, Plasmasphere, electrodynamics (RCM‐CTIPe) simulation. They interpreted the reason as a transportation of ionospheric plasmas to a higher altitude where the recombination rate is low by the equatorward neutral wind (e.g., Prölss, 1997).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This time difference is almost consistent with our observational results. Ferdousi et al (2019) also showed that the electron density enhancement appeared in the daytime (10:00–16:00 MLT) midlatitude region (50–60° GMLAT) in the results of the physics‐based Rice Convection Model‐Coupled Thermosphere, Ionosphere, Plasmasphere, electrodynamics (RCM‐CTIPe) simulation. They interpreted the reason as a transportation of ionospheric plasmas to a higher altitude where the recombination rate is low by the equatorward neutral wind (e.g., Prölss, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…Many previous studies on the response of the magnetosphere, ionosphere, and thermosphere associated with solar wind disturbances and geomagnetic storms using ground‐based and satellite observations and simulation have been conducted (e.g., Aa et al, 2019; Astafyeva et al, 2016; Blanc & Richmond, 1980; Bruinsma & Forbes, 2007; David et al, 2011; Ferdousi et al, 2019; Huang, 2008; Kikuchi et al, 1996, 2008; Liu, Wang, Burns, Yue, et al, 2016; Liu, Wang, Burns, Solomon, et al, 2016; Nishida, 1968; Sori et al, 2019; Tanaka, 1995; Tanaka et al, 2016). According to previous knowledge, when the southward IMF arrives at the magnetopause and the merging process between the IMF and geomagnetic field occurs at the dayside magnetopause, the solar wind energy effectively enters the magnetosphere and the intensity of FACs and high‐latitude convection is enhanced significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These magnetic latitude aligned velocities, with latitudinal width of a few degrees, formed a clear signature of a Space Weather 10.1029/2019SW002325 strong SAPS (Foster & Burke, 2002). Studies have found that SAPS can directly accelerate the background zonal wind via strong ion drag (e.g., Ferdousi et al, 2019;Wang et al, 2011;Zhang et al, 2015) and can indirectly change the meridional wind through the Coriolis force (Zhang et al, 2015). A large storm enhanced density (SED) plume was also observed during this time frame but emerged prior to the SAPS launch at Millstone Hill latitudes, with SED plume and Tongue of Ionization (TOI) structures persisting for a few hours (Figure 6).…”
Section: Concurrent Mstids and Lsstidsmentioning
confidence: 99%
“…These results suggest that SAPS-related strong westward ion drift might have induced the enhancement of LSSTID westward propagation components and may have even excited MSTIDs. They modified the TAD (AGW) associated with the LSSTID due to changing thermospheric winds (Ferdousi et al, 2019;Wang et al, 2011;Zhang et al, 2015), composition and temperature conditions (Guo et al, 2018;Wang et al, 2012) as a result of SAPS induced ion-neutral coupling. The presence of SAPS channels during the September event provided several potential impacts relevant to TID dynamics.…”
Section: Concurrent Mstids and Lsstidsmentioning
confidence: 99%